A framework to manage the measurable, immeasurable and the unidentifiable financial risk. (February 2014) - Ganegoda, Amandha; Evans, John
Traditionally, financial risk management has mainly focused on the types of risk that can be identified and measured. Many actuarial and statistical theories and models have been developed in the past, to quantify such risks. However, high-profile events such as Black Monday, the Asian financial crisis, 9/11 terrorist attacks, the Enron scandal, and more recently the global financial crisis, has repeatedly proven to the financial world that risks which matter to the stability of financial firms are often immeasurable and unidentifiable. Hence, simply focusing on the measurable risks is inadequate for a sound management of financial risks. In this paper, we develop a holistic framework to identify (if possible), measure (if possible), and manage the measurable, as well as the immeasurable, and the unidentifiable risks. We identify four realms of financial uncertainties and point out that each realm possesses a unique set of challenges to risk management. Moreover, we show that the tools needed to grapple each realm of uncertainty are fundamentally different, therefore stressing the importance of the need for awareness of these separate realms of uncertainty. The paper provides a discussion of methods available for assessing and managing each realm of uncertainty, and their limitations, by drawing from risk management techniques used in various fields of science and other industries.